"He passed away because of cutting down a fig tree": The similarity between people and trees in Jewish symbolism, mysticism and halakhic practice - Shemesh, Abraham O. (HTS teologiese studies, 2020)
Comparing people to trees is a customary and common practice in Jewish tradition. The current article examines the roots and the development of the image of people as trees in Jewish sources, from biblical times to recent generations (Bible, classical rabbinical literature, medieval to modern rabbinic literature and popular culture), as related to the prohibition against destroying fruit trees. The similarity between humans and trees in the Jewish religion and culture was firstly suggested in biblical literature as a conceptual-symbolic element. However, since the Amoraic period (3rd–5th centuries CE), this similarity was transformed to a resemblance bearing mystical and Halakhic (Jewish Law) implications. Various sources in rabbinical literature describe trees as humans that may be spoken to or yelled at to produce fruit. Cutting down a tree was perceived by the rabbis of the Talmud (3rd–5th centuries CE) not only as an unethical act or vandalism, but also as a hazard: the death of the tree corresponds to the death of the person who resembles it. All societies, cultures and religions have a system of values and practices that are aimed at shaping people, society and the environment according to a certain worldview.Contribution: The discussion in this article on the relationship between religion-culture and nature (plants) indicates how the Jewish religion shaped believers’ attitude to the world of flora over the generations by transforming the man-tree comparison into one with binding and even threatening practical religious meaning.